Selection of Reference Genes for Quantitative Real-Time PCR during Flower Development in Tree Peony (Paeonia suffruticosa Andr.) - Li, Jian; Han, Jigang; Hu, Yonghong; Yang, Ji (Frontiers in Plant Science, 2016)
Tree peony (Paeonia suffruticosa) is a perennial plant indigenous to China known for its elegant and vibrantly colorful flowers. A few genes involved in petal pigmentation have been cloned in tree peony. However, to date, there have been few studies on the comparison and selection of stable reference genes for gene expression analysis by quantitative reverse-transcription PCR (qRT-PCR) in this species. In this study, 10 candidate reference genes were evaluated for the normalization of qRT-PCR in three tree peony cultivars. GAPDH and UBC were identified as the top two most stable reference genes in ‘Feng Dan’ and ‘Xi Shi’, and EF-1α/UBC was recommended to be the best combination for ‘Que Hao’. The expression stability of various reference genes differed across cultivars, suggesting that selection and validation of reliable reference genes for quantitative gene expression analysis was necessary not only for different species but also for different cultivars. The results provided a list of reference genes for further study on gene expression in P. suffruticosa. However, in any case, a preliminary check on the accuracy of the best performing reference genes is requested for each qRT-PCR experiment.